Experimental and theoretical investigations of pile and penetrometer installation in clay - Gill, David R. (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2000)
This thesis advances our understanding of the type of ground movements and strains that take place during installation of closed-ended piles and penetrometers in clay, with particular reference to penetrometers with flat and 60° conical tips. This was to be achieved by; (a) conducting model experiments to measure the displacements around penetrating penetrometers and (b) the development of a numerical/theoretical model.
Keywords: Civil Structural and Environmental Engineering, Ph.D.; Ph.D. Trinity College Dublin